2021
DOI: 10.1039/d0gc04050a
|View full text |Cite
|
Sign up to set email alerts
|

In situ self-organization of uniformly dispersed Co–N–C centers at moderate temperature without a sacrificial subsidiary metal

Abstract: M-N-C centers have garnered tremendous research attention due to a potential replacement to the Pt- group metal based cathode catalysts and is expected to be the integral part of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 72 publications
1
36
0
Order By: Relevance
“…For this study, we have considered a batch of four electrocatalysts prepared by pyrolyzing dicyandiamide (DCDA, 200 mg) and Co phthalocyanine (CoPc, 50 mg). The detailed synthesis process is discussed in ref 19. A S7 and S8, and Table 1), it is found that CoP750 is much more effective at facilitating ORR followed by CoP900, CoP600, and CoP380 under identical experimental conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…For this study, we have considered a batch of four electrocatalysts prepared by pyrolyzing dicyandiamide (DCDA, 200 mg) and Co phthalocyanine (CoPc, 50 mg). The detailed synthesis process is discussed in ref 19. A S7 and S8, and Table 1), it is found that CoP750 is much more effective at facilitating ORR followed by CoP900, CoP600, and CoP380 under identical experimental conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…CoPT's (T = 380/600/750/ 900) were synthesized by the pyrolysis of dicyandiamide (DCDA, 200 mg, mainly a nitrogen and carbon source) and cobalt phthalocyanine (CoP as a cobalt precursor), as discussed in our recent report. 19 The pyrolysis temperatures used are 380, 600, 750, and 900 °C. The temperature ramping rate used was 10 °C/min with a dwell time of 3 h. A physical mixture of DCDA and CoP was prepared by grinding them via a mortar and pestle.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[29][30][31] Reports suggest that metal-nitrogen coordination (M-N x ) centers are highly beneficial for ORR and HER. [32][33][34][35][36][37] Transition metal nanoparticles supported on N-doped carbon have been extensively studied for HER. [38][39][40] Metal nanoparticles optimize the surface states of M-N x thereby reducing the energy barrier for water dissociation.…”
mentioning
confidence: 99%